2024
DOI: 10.32604/or.2023.046582
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in breast cancer diagnosis, treatment and prognosis

XIAOJIA HUANG,
CAILU SONG,
JINHUI ZHANG
et al.

Abstract: Breast cancer has surpassed lung cancer to become the most common malignancy worldwide. The incidence rate and mortality rate of breast cancer continue to rise, which leads to a great burden on public health. Circular RNAs (circRNAs), a new class of noncoding RNAs (ncRNAs), have been recognized as important oncogenes or suppressors in regulating cancer initiation and progression. In breast cancer, circRNAs have significant roles in tumorigenesis, recurrence and multidrug resistance that are mediated by various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Over the past few decades, circRNAs have gradually become the focus of research on various diseases due to their unique properties. Advancements in high-throughput RNA sequencing and circRNA-specific molecular tools have revealed that numerous circRNAs are abnormally expressed in a wide spectrum of cancer types, suggesting potential functional roles of these circRNAs in cancers [ 42 ]. The noncoding functions of circRNAs, including their functions as miRNA-binding sponges and interactions with RBPs, have been the most extensively studied in the field of circRNA investigation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, circRNAs have gradually become the focus of research on various diseases due to their unique properties. Advancements in high-throughput RNA sequencing and circRNA-specific molecular tools have revealed that numerous circRNAs are abnormally expressed in a wide spectrum of cancer types, suggesting potential functional roles of these circRNAs in cancers [ 42 ]. The noncoding functions of circRNAs, including their functions as miRNA-binding sponges and interactions with RBPs, have been the most extensively studied in the field of circRNA investigation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, circRNAs have been identified that may serve as promising targets of therapeutic strategies for diseases due to their high stability and the characteristic of tissue‐ or cell type‐specific expression. 24 , 25 Moreover, circRNA‐based vaccines, such as CircRNA RBD , VFLIP‐X, cytokine‐encoding circular mRNA for cancer therapy, and CircRNA OVA‐luc ‐LNP vaccine, have been proposed and confirmed in animal models. 26 Therefore, targeting circST6GAL1 may be a promising strategy for preventing PAH.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stage of tumors, E2F1 promotes both cell proliferation and apoptosis and has been shown to delay tumor progression. In more advanced stages, the proapoptotic function is gradually lost, and thus the proliferative effect of E2F1 becomes dominant [ 52 , 53 ]. Consistent with previous studies, the bioinformatic analyses in our study revealed that both the 3′-UTR of E2F1 and circMYBL2 contain miR-1205 binding sites, and western blotting further indicated that circMYBL2 regulates E2F1 expression by sponging miR-1205.…”
Section: Discussionmentioning
confidence: 99%